Shear Strength Characteristics And Microcrack Pattern Of Granite From Pos Selim, Perak, Malaysia - Mohd Pauzi, Nur Irfah (2007)

(untitled)
Granite bodies can fracture in various characteristic ways relative to the density of fractures, the number of joints sets and their distribution, and the type of fractographic features on fracture surfaces. Granite commonly involves complex composite microcrack systems which are caused by different geologic processes under varying condition. Microscopic studies of cracks under shear stress in granite samples have been carried out using Robertson shear testing and Scanning Electron Microscope (SEM) to study the shear strength parameters and their interaction between microcrack propagation patterns. Shear strength parameters such as friction angle and cohesion, Joint Roughness Coefficient (JRC) and Joint Compressive Strength (JCS) has been studied on granite at Pos Selim area. Microcrack propagation patterns for granite at Pos Selim has been proposed to be categorized into two type which are type A and type B. Type A is microcrack propagation pattern for granite grade II and type B is microcrack propagation pattern for granite grade III. Griffith theory states that fracture material is caused by stress concentration, causing the crack to propagate and ultimately contributing to microscopic failure of the material. The result show that type A and type B microcrack propagation patterns do comply with Griffith theory. Type A microcrack propagation pattern does not lead to failure and consists of minor crack surface. This is because type A material has higher strength compared to type B. Type B material show microcrack pattern that propagates from the left side of the sample leading towards the right side of the sample which caused failure of the material. The relationship between the microcrack pattern and the shear strength parameters proves that an increase in shear stress and normal stress would result in increase of microcrack area. Therefore, the knowledge from these studies show that the understanding in microcrack propagation patterns can improve our understanding of damaging process and failure of intact rock.